Pathways to Near-Zero Plagiarism Level in English Research Article Writing: A Photovoice Autophenomenographic Insight - Mudra, Heri (LET: Linguistics, Literature and English Teaching Journal, 2025)
Many academic authors expect plagiarism-free writing to contribute to developing academic integrity, but dishonest practices, such as plagiarism, in English research articles remain unavoidable. This study records the author’s perennial challenges in combatting plagiarism to reach a near-zero level when writing an English research article. It also documents the author’s emotional expressions through a visual image to represent the physical experiences. This study integrates two data collection methods, including autophenomenograpy and photovoice, respectively. The results reveal several challenges encountered in decreasing plagiarism levels, including in the search for credible sources, literature conceptualisation, utilisation of free vs paid plagiarism checkers, co-authorship empowerment, and preference for prestige. Emotional expressions reflected through selected images (i.e., bush, unfinished house, doll as a team, dollar symbol, and graduation cap) lead to academic solutions, such as careful literature selection, critical thinking, reliance on the premium version of plagiarism checker, co-authorship task division, and self-writing discipline. In addition, recommendations for university stakeholders and teachers are discussed, bridging the gap between near-zero plagiarism levels and research article writing.